2017
DOI: 10.1002/1873-3468.12825
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and functions of docosahexaenoic acid‐containing membrane glycerophospholipids

Abstract: Omega‐3 (ω‐3) fatty acids (FAs) such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are known to have important roles in human health and disease. Besides being utilized as fuel, ω‐3 FAs have specific functions based on their structural characteristics. These functions include serving as ligands for several receptors, precursors of lipid mediators, and components of membrane glycerophospholipids (GPLs). Since ω‐3 FAs (especially DHA) are highly flexible, the levels of DHA in GPLs may affect memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 127 publications
0
81
0
Order By: Relevance
“…FAs are classified, according to the presence of double bonds in their chain structure, as saturated FAs (SFAs) in the absence of double bonds, as monounsaturated fatty acids (MUFAs) when a single double bond is present, and as polyunsaturated FAs (PUFAs) when having two or more double bonds. The position of double bonds in unsaturated FA is often written using the n-x notation where x indicates the position of the first carbon with a double bond counting from the methyl end of the chain (n-) [8,9]. Membrane fluidity, flexibility, fusion, fission, and curvature largely depend on the FA composition of phospholipids [10].…”
Section: Introductionmentioning
confidence: 99%
“…FAs are classified, according to the presence of double bonds in their chain structure, as saturated FAs (SFAs) in the absence of double bonds, as monounsaturated fatty acids (MUFAs) when a single double bond is present, and as polyunsaturated FAs (PUFAs) when having two or more double bonds. The position of double bonds in unsaturated FA is often written using the n-x notation where x indicates the position of the first carbon with a double bond counting from the methyl end of the chain (n-) [8,9]. Membrane fluidity, flexibility, fusion, fission, and curvature largely depend on the FA composition of phospholipids [10].…”
Section: Introductionmentioning
confidence: 99%
“…In E0771 xenografts, it is of interest to note that DHA level was increased approximately 4.5fold with MAG-DHA intervention. It is known that the enrichment of DHA with high unsaturation in membranes makes cancer cells more sensitive to free radicals because it makes the membrane less rigid and more vulnerable [12]. Therefore, in the present study, the cell death induced by MAG-DHA was largely mediated by increased lipid peroxidation in cancer cells.…”
Section: Discussionmentioning
confidence: 59%
“…The fatty acid composition of cellular membranes can modify permeability (Imen et al, 2013;Palacios, Bonilla, Perez, Racotta, & Civera, 2004). Huster, Jin, Arnold, and Gawrisch (1997), Hishikawa, Valentine, Iizuka-Hishikawa, Shindou, and Shimizu (2017), and Cornet et al (2018) reported that high levels of PUFA, such as DHA, could make membranes thin, flexible and fluid, while Morris, Lockwood, and Dawson (1982) reported the possible relationship between decreased permeability and increased SFA in the gills of amphipod crustaceans (Gammarus duebeni). From another point of view, the accumulation of n-3 PUFA, especially EPA and DHA, can alter the membrane microenvironment and thereby enhance NKA activity (Bell et al, 1997;Bystriansky & Ballantyne, 2007;Grant et al, 2008 It is generally believed that when external salinity is altered, the response of serum osmolality in teleost fish can be divided into two stages: first, a passive increase or decrease in serum osmolality occurs depending on the environment; second, osmolality begins to recover through physiological regulation and remains stable (Sturrock, Hunter, Milton, & Trueman, 2013;Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%